Principal Leadership in the Era of Educational Digitalization and Its Impact on Teacher Performance in Madrasahs - Ranosa, M. Risky; Qiftiyah, Maratul; Syauqi, Muammar (Universitas Islam Negeri Raden Intan Lampung, 2025)
Madrasah principal leadership plays a strategic role in enhancing teacher performance amid educational digitalization. This study aims to describe how the principal’s leadership improves teacher performance at MTs Negeri 2 Bandar Lampung. Using a descriptive qualitative approach, data were collected over three months (February–April 2024) from 12 participants including the principal, 10 teachers, and one curriculum deputy principal selected via purposive sampling. Data collection employed semi-structured interviews, participatory observation, and documentation, followed by thematic analysis based on Miles, Huberman, and Saldaña’s (2014) framework. Findings reveal that the principal enhances teacher performance through four integrated strategies: (1) influencing by monitoring lesson plans and organizing online learning training; (2) mobilizing through exemplary discipline and professional conduct; (3) motivating by requiring teaching activities to be conducted on campus; and (4) mentoring by granting pedagogical autonomy while enforcing disciplinary measures. These practices reflect an integrative application of transformational, instructional, and distributed leadership models, fostering a collaborative, innovative, and digitally adaptive school culture. The study confirms that effective principal leadership not only boosts teacher performance but also cultivates a conducive work environment aligned with quality Islamic education goals in the digital era.